A Remote Lab to Simulate the Physiological Process of Ingestion and Excretion of a Drug - Cardoso, Alberto; Osório, Daniel; Leitão, Joaquim; Sousa, Vitor; Teixeira, César (International Journal of Online and Biomedical Engineering (iJOE), 2016)
Remote and virtual labs represent a very important support for online experimentation in engineering courses and can be used to improve the students learning process, providing, for example, experiments to simulate physiological processes in Biomedical Engineering subjects. This paper presents an online experiment, supported by a three-tank lab system to simulate an equivalent model of the physiological process of ingestion and excretion of a drug. A Web platform is used to interact with the remote and virtual labs, where students can visualize and obtain data in real time from the remote system and observe the dynamic behavior of the system considering a virtual representation.